An experimental study on the mobility of droplets in liquid-liquid Taylor flows within circular capillaries. (December 2022) - Zadeh, Seyyed Saeed Shojaee; Egan, Vanessa; Walsh, Pat
Highlights: An experimental study was performed to investigate droplet mobility in Taylor flows. A novel, fully automated, experimental setup was designed for droplet measurement. Above a certain L D / D threshold, droplet velocity becomes independent of its length. Buoyancy forces are shown to greatly impact the mobility of short droplets. A new correlation is presented to better estimate the velocity of elongated droplets. Abstract: Further development of microfluidics devices that reply on liquid-liquid droplet flows, requires a thorough understanding of the parameters influencing droplet velocity. This study provides greater insights into this subject through an analysis of parameters effecting droplet mobility in such flows. A novel, fully automated experimental setup was designed to accurately measure droplet velocity and length. Measurements were performed over a wide range of Capillary number ( 2 × 10 − 4 to 3.7 × 10 − 2 ), Bond number ( 0.05 to 3.2 ) and carrier to dispersed viscosity ratio ( 0.059 to 23.2 ) while also varying droplet length. Five different fluid combinations were examined within circular capillaries with inlet diameters ranging from 555 μ m to 1.70 m m . Results reveal a complex relationship between droplet velocity and droplet length, viscosity ratio and Bond number. In all cases, as droplet length exceeds a threshold value, droplet velocity becomes independent of length and is shown to scale with ∼ Ca 0.5 . As the droplet length falls below the threshold, the droplet velocity faces a changeover zone in which the velocity initially declines and then rises by further increase in the length. For shorter droplets, higher Bond numbers cause the droplet phase to travel asymmetrically with respect to the channel centre line which substantially impacts the mobility of these droplets. Finally, a new expression has been developed to estimate the velocity of elongated droplets.